The Sense Shaping of Taste in Composite Writing-- An Example of "Spicy" Presentation - Ji Han (Sinolingua: Journal of Chinese Studies, 2024)
The integration of multimodal elements in contemporary writing practices has transformed the way sensory experiences are conveyed and internalized by audiences. This study illuminates the mechanisms through which composite writing shapes the sensory experience of taste, with a particular emphasis on the perception of spiciness. By examining composite writings from various media platforms, we uncover the intricate relationship between media representation and sensory perception. Our theoretical framework is anchored in the concepts of synesthesia, metaphor theory, and media studies, particularly the influential ideas of Marshall McLuhan on media extensions and human experience. The study lies in its exploration of how composite writing not only reflects but also shapes the audience's sensory experiences. We argue that the metaphorical use of spiciness in composite writing extends beyond the gustatory to encompass cultural and personal identities, challenging traditional hierarchies of sensory experience in aesthetic discourse.